First report of melon and cucumber plants as natural hosts of cowpea mild mottle virus - B. A. Silva; C. M. Kauffmann; S. B. S. Cardenas; P. S. Queiroz; A. M. V. Batista; H. B. S. Mota; A. K. Inoue-Nagata; D. M. S. Freitas; Tatsuya Nagata (Journal of Plant Pathology, 2026)

Consensus Paper: Models of Cerebellar Functions - Shinji Kakei; Andreea C. Bostan; Timothy J. Ebner; Mohammad Amin Fakharian; Hiroaki Gomi; Xavier Guell; Marie Hemelt; Huu Hoang; Court Hull; Masato Inoue; Takahiro Ishikawa; Masashi Kameda; et al. (The Cerebellum, 2026)

Modelling free residual chlorine decay in a residential district water distribution network using smart water meter data - S. Obaid; K. Hosoi; N. M. Ngoc; T. Inoue; K. Yokota (International Journal of Environmental Science and Technology, 2025)
Chlorine is the most common disinfectant in drinking water worldwide, and the free residual chlorine concentration has been stipulated at least 0.1 mg/L according to Japanese drinking water standard to ensure disinfection efficacy during distribution. In addition, Japan is also applying approximately 0.4 mg/L chlorine at treatment plants to supply tasty drinkable water to residents. Although a concentration lower than 0.4 mg/L can help avoid an unpleasant chlorine taste in the supply water, it raises challenges for maintaining residual chlorine greater than the standard throughout distribution pipelines. The chlorine concentration decreases along distribution pipes because of bulk decay and wall decay. These decays depend on the initial chlorine concentration, temperature, time, pipe material, etc. Therefore, bottle tests with the Arrhenius theory were set up on the water at the distribution inlet in the Chibata district in Kosai city, Japan at various temperatures and times to measure the bulk decay coefficient. A literature review and root square mean error matching field data were conducted to estimate the wall decay coefficient. These decay coefficients were input into EPANET 2.2 to simulate water quality using smart water meters’ hourly consumption data. Therefore, the points where chlorine concentrations were below the standard could be hourly estimated.

P19-40 Risk assessment of AFB1 due to CYP3A4-mediated biotransformation with a highly sensitive human intestinal model - L. Bai; K. Tachibana; M. Murata; T. Inoue; H. Mizuguchi; S. Maeda; K. Ikemura; M. Okuda; T. Kusakabe; M. Kondoh (Toxicology Letters, 2024)

Performance of Saccharomyces cerevisiae strains against the application of adaptive laboratory evolution strategies for butanol tolerance - Suéllen P.H. Azambuja; Allan H.F. de Mélo; Bruno G. Bertozzi; Heitor P. Inoue; Viviane Y. Egawa; Carlos A. Rosa; Liliana O. Rocha; Gleidson S. Teixeira; Rosana Goldbeck (Food Research International, 2024)

DNA barcodes reliably differentiate between nivicolous species of Diderma (Myxomycetes, Amoebozoa) and reveal regional differences within Eurasia - Oleg N. Shchepin; Ángela López Villalba; Maho Inoue; Ilya S. Prikhodko; Daria A. Erastova; Mikhail V. Okun; Jan Woyzichovski; Yuka Yajima; Vladimir I. Gmoshinskiy; Gabriel Moreno; Yuri K. Novozhilov; Martin Schnittler (Protist, 2024)

Preliminary analysis focusing on in-vessel thermal hydraulics in loss-of-heat removal systems in a sodium-cooled fast reactor - H. Sonoda; S. Fujita; M. Inoue; T. Okawa (Annals of Nuclear Energy, 2023)

Distribution of natural radionuclides in NORM samples from North Abu Rusheid area, Egypt - S. Sakr; K. Inoue; A. Mohamed; A.A. Ahmed; M.G. ElFeky; G.M. Saleh; M.S. Kamar; H. Arae; T. Aono; S.K. Sahoo (Journal of Environmental Radioactivity, 2023)

P03-12: In vivo mutagenicity assessment and derivation of reference dose of styrene - Y. Murata; M. Matsumoto; T. Iso; Y. Shigeta; S. Hasegawa; T. Umano; N. Hirose; K. Horibata; K.-I. Sugiyama; K. Inoue; A. Hirose; K. Masumura (Toxicology Letters, 2023)

The DiSCPersal model: A simple model for the small-scale atmospheric transport of spheroidal carbonaceous particles (SCPs) - Richard S. Vachula; Ann Sullivan Ojeda; Emma D. Henderson; Jun Inoue (Chemosphere, 2023)

Nanopore sequencing of tomato mottle leaf distortion virus, a new bipartite begomovirus infecting tomato in Brazil - Thais P. Martins; Tadeu A. Souza; Patricia S. da Silva; Erich Y. T. Nakasu; Fernando L. Melo; Alice K. Inoue-Nagata; Tatsuya Nagata (Archives of Virology, 2021)

Area-wide insecticide resistance and endosymbiont incidence in the whitefly Bemisia tabaci MEAM1 (B biotype): A Neotropical context - R. A. C. Dângelo; M. Michereff-Filho; A. K. Inoue-Nagata; P. S. da Silva; M. Chediak; R. N. C. Guedes (Ecotoxicology, 2021)

Enhanced vertical turbulent nitrate flux in the intermediate layer of the Kuroshio in the Tokara Strait - T. Tanaka; D. Hasegawa; I. Yasuda; D. Yanagimoto; S. Fujio; H. Nakamura; R. Inoue; J. Nishioka (Journal of Oceanography, 2021)

Correction to: Herding mechanisms to maintain the cohesion of a harem group: two interaction phases during herding - Monamie Ringhofer; Clark Kendrick Go; Sota Inoue; Renata S. Mendonça; Satoshi Hirata; Takatomi Kubo; Kazushi Ikeda; Shinya Yamamoto (Journal of Ethology, 2021)
The article Herding mechanisms to maintain the cohesion of a harem group.

Feral horses’ (Equus ferus caballus) behavior toward dying and dead conspecifics - Renata S. Mendonça; Monamie Ringhofer; Pandora Pinto; Sota Inoue; Satoshi Hirata (Primates, 2020)

Herding mechanisms to maintain the cohesion of a harem group: two interaction phases during herding - Monamie Ringhofer; Clark Kendrick Go; Sota Inoue; Renata S. Mendonça; Satoshi Hirata; Takatomi Kubo; Kazushi Ikeda; Shinya Yamamoto (Journal of Ethology, 2020)
In animal groups, individual interactions achieve coordinated movements to maintain cohesion. In horse harem groups, herding is a behavior in which males chase females from behind; it is considered to assist with group cohesiveness. However, the mechanisms by which the individuals move to maintain group cohesion are unknown. We applied novel non-invasive methods of drone filming and video tracking to observe horse movements in the field with high temporal and spatial resolution. We tracked all group members and drew trajectories. We analyzed the movements of females and found two phases of interactions based on their timing of movement initiation. The females that moved first were those nearest to the herding male, while the movement initiation of the later females was determined by the distance from the nearest moving female, not by the distance from the herding male. These interactions are unique among animal group movements and might represent a herding mechanism responsible for maintaining group cohesion. This might be due to long-term stable relationships within a harem group and strong social bonds between females. This study showed that the combination of drone filming and video tracking is a useful method for analyzing the movements of animals simultaneously in high resolution.

Correction to: spatial positioning of individuals in a group of feral horses: a case study using drone technology - Sota Inoue; Shinya Yamamoto; Monamie Ringhofer; Renata S. Mendonça; Carlos Pereira; Satoshi Hirata (Mammal Research, 2019)

Spatial positioning of individuals in a group of feral horses: a case study using drone technology - Sota Inoue; Shinya Yamamoto; Monamie Ringhofer; Renata S. Mendonça; Carlos Pereira; Satoshi Hirata (Mammal Research, 2019)

Improving the standards for gut microbiome analysis of fecal samples: insights from the field biology of Japanese macaques on Yakushima Island - Takashi Hayakawa; Akiko Sawada; Akifumi S. Tanabe; Shinji Fukuda; Takushi Kishida; Yosuke Kurihara; Kei Matsushima; Jie Liu; Etienne-Francois Akomo-Okoue; Waleska Gravena; Makoto Kashima; Mariko Suzuki; et al. (Primates, 2018)

High-throughput sequencing reveals a novel closterovirus in arracacha (Arracacia xanthorrhiza) - Anelise F. Orílio; Rosana Blawid; Gabriela A. Costa; Suzane S. V. S. F. Gomes; Tatsuya Nagata; Nuno R. Madeira; Alice K. Inoue-Nagata; Renato O. Resende (Archives of Virology, 2018)

Drought stress during soybean seed filling affects storage compounds through regulation of lipid and protein metabolism - Andressa C. S. Nakagawa; Haruka Itoyama; Yuri Ariyoshi; Nobuyuki Ario; Yuki Tomita; Yukari Kondo; Mari Iwaya-Inoue; Yushi Ishibashi (Acta Physiologiae Plantarum, 2018)

Sources of resistance to Potato virus Y and Pepper yellow mosaic virus in Solanum (section Lycopersicon) germplasm - Renata M. Oliveira; Érico C. Dianese; Mirtes F. Lima; Renato O. Resende; Alice K. Inoue-Nagata; Leonardo S. Boiteux (European Journal of Plant Pathology, 2018)

Complete genome sequence of melon yellowing-associated virus from melon plants with the severe yellowing disease in Brazil - Thiago M. Costa; Rosana Blawid; Avanor C. da Costa Junior; Mirtes F. Lima; Fernando A. S. de Aragão; Genira P. de Andrade; Gilvan Pio-Ribeiro; Miguel A. Aranda; Alice K. Inoue-Nagata; Tatsuya Nagata (Archives of Virology, 2017)

Comparison of the social systems of primates and feral horses: data from a newly established horse research site on Serra D’Arga, northern Portugal - Monamie Ringhofer; Sota Inoue; Renata S. Mendonça; Carlos Pereira; Tetsuro Matsuzawa; Satoshi Hirata; Shinya Yamamoto (Primates, 2017)

Spatial variation in low-level 134Cs in the coastal sediments off central Honshu in the Sea of Japan: implications for delivery, migration, and redistribution patterns - Mutsuo Inoue; H. Uemura; H. Kofuji; K. Fujimoto; H. Takata; Y. Shirotani; N. Kudo; S. Nagao (Journal of Oceanography, 2017)

Factors affecting water availability for high Arctic lichens - T. Inoue; S. Kudoh; M. Uchida; Y. Tanabe; M. Inoue; H. Kanda (Polar Biology, 2017)

Nitrogen manipulation affects leaf senescence during late seed filling in soybean - Md. Matiul Islam; Yushi Ishibashi; Andressa C. S. Nakagawa; Yuki Tomita; Xin Zhao; Mari Iwaya-Inoue; Susumu Arima; Shao-Hui Zheng (Acta Physiologiae Plantarum, 2017)

Simultaneous spawning by female stream goby Rhinogobius sp. and the association with brood cannibalism by nesting males - S. Ito; H. Iwao; J. Sakata; M. Inoue; K. Omori; Y. Yanagisawa (Journal of Fish Biology, 2016)
A laboratory experiment was conducted by varying the undersurface area of nesting substratum and the number of females in an experimental tank to elucidate the determinants of the mating pattern in the stream goby, Rhinogobius sp. cross‐band type. Males with larger nests tended to attract two or more females to their nest in a tank. Moreover, males spawned simultaneously with multiple females and entire brood cannibalism by males was rarely observed under a female‐biased sex ratio. When males spawned with a single female with low fecundity, however, entire brood cannibalism occurred at a high frequency, suggesting that a male guarding a nest with fewer eggs consumes the brood. Therefore, spawning behaviour of females that leads to a large egg mass would decrease the risk of entire brood cannibalism. In this species, simultaneous spawning by multiple females in a nest serves as a female counter‐measure against entire brood cannibalism. These results suggest that a conflict of interest between the sexes through brood cannibalism is a major determinant of simultaneous spawning.

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

The importance of primary inoculum and area-wide disease management to crop health and food security - A. Bergamin Filho; A. K. Inoue-Nagata; R. B. Bassanezi; J. Belasque; L. Amorim; M. A. Macedo; J. C. Barbosa; L. Willocquet; S. Savary (Food Security, 2016)

Holocene uplifted coral reefs in Lanyu and Lutao Islands to the southeast of Taiwan - S. Inoue; H. Kayanne; N. Matta; W. S. Chen; Y. Ikeda (Coral Reefs, 2011)

Search in Solanum (section Lycopersicon) germplasm for sources of broad-spectrum resistance to four Tospovirus species - É. C. Dianese; M. E. N. Fonseca; A. K. Inoue-Nagata; R. O. Resende; L. S. Boiteux (Euphytica, 2011)

Audit and improve! Evaluation of a real-time probe-based PCR assay with internal control for the direct detection of Mycobacterium tuberculosis complex - M. Inoue; W. Y. Tang; S. Y. Wee; T. Barkham (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Analysis of the triple gene block sequence in an important melon pathogen, Melon yellowing-associated virus - Tatsuya Nagata; Luisa S. Dutra; Priscila A. Oliveira; Antonio C. de Ávila; Alice K. Inoue-Nagata (Journal of General Plant Pathology, 2010)

Natural infection of Nicandra physaloides by Tomato severe rugose virus in Brazil - Julio C. Barbosa; Sarah S. Barreto; Alice K. Inoue-Nagata; Marcelo S. Reis; Ana Carolina Firmino; Armando Bergamin Filho; Jorge Alberto Marques Rezende (Journal of General Plant Pathology, 2009)

Changes in fire regimes since the Last Glacial Maximum: an assessment based on a global synthesis and analysis of charcoal data - M. J. Power; J. Marlon; N. Ortiz; P. J. Bartlein; S. P. Harrison; F. E. Mayle; A. Ballouche; R. H. W. Bradshaw; C. Carcaillet; C. Cordova; S. Mooney; P. I. Moreno; et al. (Climate Dynamics, 2008)

Temporal variations in ozone concentrations derived from Principal Component Analysis - S. Yonemura; S. Kawashima; H. Matsueda; Y. Sawa; S. Inoue; H. Tanimoto (Theoretical and Applied Climatology, 2008)

Natural infection of Alternanthera tenella (Amaranthaceae) by a new potyvirus - A. M. R. Almeida; C. Y. Fukushigue; F. Sartori; E. Binneck; S. R. R. Marin; A. K. Inoue-nagata; C. M. Chagas; E. R. Souto; T. Mituti (Archives of Virology, 2007)

Identification and characterization of RNA-dependent RNA polymerase activity in recombinant Japanese encephalitis virus NS5 protein - F. Yu; F. Hasebe; S. Inoue; E. G. M. Mathenge; K. Morita (Archives of Virology, 2007)

Evolutionary trend of phylogenetic diversity of nitrogen fixation genes in the gut community of wood‐feeding termites - A. YAMADA; T. INOUE; S. NODA; Y. HONGOH; M. OHKUMA (Molecular Ecology, 2007)
Nitrogen fixation by gut microorganisms is one of the crucial aspects of symbiosis in wood‐feeding termites since these termites thrive on a nitrogen‐poor diet. In order to understand the evolution of this symbiosis, we analysed the nitrogenase structural gene nifH in the gut microbial communities. In conjunction with the published sequences, we compared approximately 320 putatively functional NifH protein sequences obtained from a total of 19 termite samples that represent all the major branches of their currently proposed phylogeny, and from one species of the cockroach Cryptocercus that shares a common ancestor with termites. Using multivariate techniques for clustering and ordination, a phylogeny of NifH protein sequences was created and plotted variously with host termite families, genera, and species. Close concordance was observed between NifH communities and the host termites at genus level, but family level relationships were not always congruent with accepted termite clade structure. Host groups examined included basal families (Mastotermitidae, Termopsidae, Kalotermitidae, as well as Cryptocercus ), the most derived lower termite family Rhinotermitidae, and subfamilies representing the advanced and highly diverse apical family Termitidae (Macrotermitinae, Termitinae, and Nasutitermitinae). This selection encompassed the major nesting and feeding styles recognized in termites, and it was evident that NifH phylogenetic divergence, as well as the occurrence of alternative nitrogenase‐type NifH, was to some extent dependent on host lifestyle as well as phylogenetic position.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Cospeciation in the triplex symbiosis of termite gut protists ( Pseudotrichonympha spp.), their hosts, and their bacterial endosymbionts - S. NODA; O. KITADE; T. INOUE; M. KAWAI; M. KANUKA; K. HIROSHIMA; Y. HONGOH; R. CONSTANTINO; V. UYS; J. ZHONG; T. KUDO; M. OHKUMA (Molecular Ecology, 2007)
A number of cophylogenetic relationships between two organisms namely a host and a symbiont or parasite have been studied to date; however, organismal interactions in nature usually involve multiple members. Here, we investigated the cospeciation of a triplex symbiotic system comprising a hierarchy of three organisms — termites of the family Rhinotermitidae, cellulolytic protists of the genus Pseudotrichonympha in the guts of these termites, and intracellular bacterial symbionts of the protists. The molecular phylogeny was inferred based on two mitochondrial genes for the termites and nuclear small‐subunit rRNA genes for the protists and their endosymbionts, and these were compared. Although intestinal microorganisms are generally considered to have looser associations with the host than intracellular symbionts, the Pseudotrichonympha protists showed almost complete codivergence with the host termites, probably due to strict transmissions by proctodeal trophallaxis or coprophagy based on the social behaviour of the termites. Except for one case, the endosymbiotic bacteria of the protists formed a monophyletic lineage in the order Bacteroidales, and the branching pattern was almost identical to those of the protists and the termites. However, some non‐codivergent evolutionary events were evident. The members of this triplex symbiotic system appear to have cospeciated during their evolution with minor exceptions; the evolutionary relationships were probably established by termite sociality and the complex microbial community in the gut.

Development of Stable Isotope Dilution Quantification Liquid Chromatography–Mass Spectrometry Method for Estimation of Exposure Levels of Bisphenol A, 4-tert-Octylphenol, 4-Nonylphenol, Tetrabromobisphenol A, and Pentachlorophenol in Indoor Air - K. Inoue; S. Yoshida; S. Nakayama; R. Ito; N. Okanouchi; H. Nakazawa (Archives of Environmental Contamination and Toxicology, 2006)

The Monitoring of Insects to Maintain Biodiversity in Ogawa Fores Reserve - S. Makino; H. Goto; T. Inoue; M. Sueyoshi; K. Okabe; M. Hasegawa; K. Hamaguchi; H. Ctanaka; I. Okochi (Environmental Monitoring and Assessment, 2006)

Expression of foreign type I ribulose-1,5-bisphosphate carboxylase/ oxygenase (EC 4.1.1.39) stimulates photosynthesis in cyanobacterium Synechococcus PCC7942 cells - T. Iwaki; K. Haranoh; N. Inoue; K. Kojima; R. Satoh; T. Nishino; S. Wada; H. Ihara; S. Tsuyama; H. Kobayashi; A. Wadano (Photosynthesis Research, 2006)

Face-selective and auditory neurons in the primate orbitofrontal cortex - Edmund T. Rolls; Hugo D. Critchley; Andrew S. Browning; Kazuo Inoue (Experimental Brain Research, 2006)

Intracolony variation of bacterial gut microbiota among castes and ages in the fungus‐growing termite Macrotermes gilvus - Y. HONGOH; L. EKPORNPRASIT; T. INOUE; S. MORIYA; S. TRAKULNALEAMSAI; M. OHKUMA; N. NOPARATNARAPORN; T. KUDO (Molecular Ecology, 2006)
The fungus‐growing termites Macrotermes cultivate the obligate ectosymbiontic fungi, Termitomyces . While their relationship has been extesively studied, little is known about the gut bacterial symbionts, which also presumably play a crucial role for the nutrition of the termite host. In this study, we investigated the bacterial gut microbiota in two colonies of Macrotermes gilvus , and compared the diversity and community structure of bacteria among nine termite morphotypes, differing in caste and/or age, using terminal restriction fragment length polymorphism (T‐RFLP) and clonal analysis of 16S rRNA. The obtained molecular community profiles clustered by termite morphotype rather than by colony, and the clustering pattern was clearly more related to a difference in age than to caste. Thus, we suggest that the bacterial gut microbiota change in relation to the food of the termite, which comprises fallen leaves and the fungus nodules of Termitomyces in young workers, and leaves degraded by the fungi, in old workers. Despite these intracolony variations in bacterial gut microbiota, their T‐RFLP profiles formed a distinct cluster against those of the fungus garden, adjacent soil and guts of sympatric wood‐feeding termites, implying a consistency and uniqueness of gut microbiota in M. gilvus . Since many bacterial phylotypes from M. gilvus formed monophyletic clusters with those from distantly related termite species, we suggest that gut bacteria have co‐evolved with the termite host and form a microbiota specific to a termite taxonomic and/or feeding group, and furthermore, to caste and age within a termite species.

Assessment of room temperature influence on finger blood flow response induced by short-term grasping of vibrating handle - M. H. Mahbub; M. Inoue; K. Yokoyama; M. S. Laskar; H. Ohnari; K. Suizu; J. Inagaki; Y. Takahashi; N. Harada (International Archives of Occupational and Environmental Health, 2006)

Effect of room temperature on percentage finger systolic blood pressure response to finger cooling - M. S. Laskar; K. Ohmura; M. Inoue; K. Yokoyama; J. Inagaki; Y. Takahashi; M. H. Mahbub; H. Ohnari; N. Harada (European Journal of Applied Physiology, 2005)

Effect of skin temperature on the ion reabsorption capacity of sweat glands during exercise in humans - A. K. M. Shamsuddin; T. Kuwahara; A. Oue; C. Nomura; S. Koga; Y. Inoue; N. Kondo (European Journal of Applied Physiology, 2005)

Induction of the metabolism of etizolam by carbamazepine in humans - S. Kondo; T. Fukasawa; N. Yasui-Furukori; T. Aoshima; A. Suzuki; Y. Inoue; T. Tateishi; K. Otani (European Journal of Clinical Pharmacology, 2005)

Findings through the AsiaFlux network and a view toward the future - S. Yamamoto; N. Saigusa; M. Gamo; Y. Fujinuma; G. Inoue; T. Hirano (Journal of Geographical Sciences, 2005)

Characterization of Oita virus 296/1972 of Rhabdoviridae isolated from a horseshoe bat bearing characteristics of both lyssavirus and vesiculovirus - K. Tanaka; Y. Sato; S. Morikawa; D. Hayasaka; M. Moriyama; T. Ono; A. Yamada; T. Kurata; T. Iwasaki; S. Inoue; S. Kanai (Archives of Virology, 2004)

Genomic analysis of immunity in a Urochordate and the emergence of the vertebrate immune system: “waiting for Godot” - Kaoru Azumi; Rosaria De Santis; Anthony De Tomaso; Isidore Rigoutsos; Fumiko Yoshizaki; Maria Rosaria Pinto; Rita Marino; Kazuhito Shida; Makoto Ikeda; Masami Ikeda; Masafumi Arai; Yasuhito Inoue; et al. (Immunogenetics, 2003)

Tandem duplication of alkaline phosphatase genes and polymorphism in the intergenic sequence in Bombyx mori - M. Itoh; T. Inoue; Y. Kanamori; S. Nishida; M. Yamaguchi (Molecular Genetics and Genomics, 2003)

Involvement of microtubules in rhizoid differentiation of Spirogyra species - K. Yoshida; N. Inoue; S. Sonobe; T. Shimmen (Protoplasma, 2003)

Nucleotide sequences of the coat protein gene of potyviruses infecting Ornithogalum thyrsoides - S. Fuji; M. Inoue; H. Yamamoto; H. Furuya; H. Naito; T. Matsumoto (Archives of Virology, 2003)

Pepper yellow mosaic virus, a new potyvirus in sweetpepper, Capsicum annuum - A. K. Inoue-Nagata; M. E. N. Fonseca; R. O. Resende; L. S. Boiteux; D. C. Monte; A. N. Dusi; A. C. de ávila; R. A. A. van der Vlugt (Archives of Virology, 2002)

Complete nucleotide sequence of the genomic RNA of Aconitum latent virus (genus Carlavirus) isolated from Delphinium sp. - S. Fuji; H. Yamamoto; M. Inoue; K. Yamashita; Y. Fukui; H. Furuya; H. Naito (Archives of Virology, 2002)

Evaluation of formation potential of trihalomethanes and mutagens due to chlorination of river water along the Kizu River in the Yodo River system in Japan - S. Sanukida; T. Nobukawa; M. Ichihara; H. Shima; K. Inoue; S. Nakachi (Limnology, 2001)

Relationships among Nicotiana species revealed by the 5S rDNA spacer sequence and fluorescence in situ hybridization - S. Kitamura; M. Inoue; N. Shikazono; A. Tanaka (Theoretical and Applied Genetics, 2001)

Karyotype analysis of Nicotiana kawakamii Y. Ohashi using DAPI banding and rDNA FISH - R. Nakamura; S. Kitamura; M. Inoue; N. Ohmido; K. Fukui (Theoretical and Applied Genetics, 2001)

Ecological Evaluation of Gadolinium Toxicity Compared with Other Heavy Metals Using an Aquatic Microcosm - S. Fuma; H. Takeda; K. Miyamoto; K. Yanagisawa; Y. Inoue; N. Ishii; K. Sugai; C. Ishii; Z. Kawabata (Bulletin of Environmental Contamination and Toxicology, 2001)

Quantitative chromosome maps and rDNA localization in the T subgenome of Nicotiana tabacum L. and its putative progenitors - S. Kitamura; M. Inoue; N. Ohmido; K. Fukui (Theoretical and Applied Genetics, 2000)

Enterobacter cowaniisp. nov., a New Species of the Family Enterobacteriaceae - Kohaku Inoue; K. Sugiyama; Y. Kosako; R. Sakazaki; S. Yamai (Current Microbiology, 2000)

Simple Aquatic Microcosm for Ecotoxicity Screening at the Community Level - S. Fuma; H. Takeda; K. Miyamoto; K. Yanagisawa; Y. Inoue; N. Ishii; K. Sugai; C. Ishii; Z. Kawabata (Bulletin of Environmental Contamination and Toxicology, 2000)

Hematite in pyrophyllite ore deposits, Shobara district, southwestern Japan - M. Ohkawa; Y. Yamashita; M. Inoue; R. Kitagawa; S. Takeno (Mineralogy and Petrology, 2000)

Subsite-specific risk factors for hypopharyngeal and esophageal cancer (Japan) - T. Takezaki; M. Shinoda; S. Hatooka; Y. Hasegawa; S. Nakamura; K. Hirose; M. Inoue; N. Hamajima; T. Kuroishi; H. Matsuura; K. Tajima (Cancer Causes & Control, 2000)

Two novel mutations of SURF1 in Leigh syndrome with cytochrome c oxidase deficiency - M. Teraoka; Y. Yokoyama; S. Ninomiya; C. Inoue; S. Yamashita; Y. Seino (Human Genetics, 1999)

Spectroscopic and electrochemical properties of two azurins (Az-iso1 and Az-iso2) from the obligate methylotroph Methylomonas sp. strain J and the structure of novel Az-iso2 - S. Suzuki; Nobuhumi Nakamura; Kazuya Yamaguchi; Kunishige Kataoka; Tsuyoshi Inoue; Nobuya Nishio; Yasushi Kai; Jiro Tobari (JBIC Journal of Biological Inorganic Chemistry, 1999)

Two novel mutations of SURF1 in Leigh syndrome with cytochrome c oxidase deficiency - M. Teraoka; Y. Yokoyama; S. Ninomiya; C. Inoue; S. Yamashita; Y. Seino (Human Genetics, 1999)

PCR-based method for identifying the S-genotypes of Japanese pear cultivars - T. Ishimizu; K. Inoue; M. Shimonaka; T. Saito; O. Terai; S. Norioka (Theoretical and Applied Genetics, 1999)

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Viruses produced from complementary DNA of virulent and avirulent strains of swine vesicular disease viruses retain the in vivo and in vitro characteristics of the parental strain - T. Kanno; T. Inoue; D. Mackay; P. Kitching; S. Yamaguchi; J. Shirai (Archives of Virology, 1998)

Reduced glutathione promotes callus growth and shoot development in a shoot tip culture of apple root stock M26 - K. Nomura; S. Matsumoto; K. Masuda; M. Inoue (Plant Cell Reports, 1998)

Short communicationRecovery from derangement of natural killer‐like activity of leucocytes due to Zn or Mn deficiency in rainbow trout, Oncorhynchus mykiss (Walbaum), by the oral administration of these elements - M Inoue; S Satoh; M Maita; V Kiron; N Okamoto (Journal of Fish Diseases, 1998)

Histopathological Changes Within the Testis Caused by Allyl Chloride Exposure in Mice - M. Zhao; M. Omura; S. Tokunaga; Y. Romero; N. Inoue (Bulletin of Environmental Contamination and Toxicology, 1998)

Tea and coffee consumption and the risk of digestive tract cancers: data from a comparative case-referent study in Japan - M. Inoue; K. Tajima; K. Hirose; N. Hamajima; T. Takezaki; T. Kuroishi; S. Tominaga (Cancer Causes & Control, 1998)

Effects of various factors including the CYP2D6 genotype and coadministration of flunitrazepam on the steady-state plasma concentrations of bromperidol and its reduced metabolite - A. Suzuki; K. Otani; K. Mihara; N. Yasui; T. Kondo; N. Tokinaga; H. Furukori; S. Kaneko; Y. Inoue; K. Hayashi (Psychopharmacology, 1998)

The Urinary Excretion of Arsenic Metabolites After a Single Oral Administration of Dimethylarsinic Acid to Rats - K. Yoshida; H. Chen; Y. Inoue; H. Wanibuchi; S. Fukushima; K. Kuroda; G. Endo (Archives of Environmental Contamination and Toxicology, 1997)

The major carotenoid in all known species of heliobacteria is the C 30 carotenoid 4,4′-diaponeurosporene, not neurosporene - S. Takaichi; Kazuhito Inoue; Mitsuhiro Akaike; Masami Kobayashi; Hirozo Oh-oka; Michael T. Madigan (Archives of Microbiology, 1997)

Cyclooxygenase inhibitors enhance the production of tissue inhibitor-1 of metalloproteinases (TIMP-1) and pro-matrix metalloproteinase 1 (proMMP-1) in human rheumatoid synovial fibroblasts - S. Takahashi; T. Inoue; M. Higaki; Y. Mizushima (Inflammation Research, 1997)

Prolactin-like immunoreactivity in the granules of neural complex cells in the ascidian Halocynthia roretzi - M. Ogawa; K. Inoue; S. Kikuyama; K. Terakado; K. Yamamoto (Cell and Tissue Research, 1997)

Interaction between carbamazepine and bromperidol - K. Otani; M. Ishida; N. Yasui; T. Kondo; K. Mihara; A. Suzuki; H. Furukori; S. Kaneko; Y. Inoue (European Journal of Clinical Pharmacology, 1997)

A possible hybrid zone in the Mytilus edulis complex in Japan revealed by PCR markers - K. Inoue; S. Odo; T. Noda; S. Nakao; S. Takeyama; E. Yamaha; F. Yamazaki; S. Harayama (Marine Biology, 1997)

Full-length genomic sequence of a hepatitis C virus genotype 2c isolate (BEBE1) and the 2c-specific PCR primers - H. Nakao; H. Okamoto; H. Tokita; T. Inoue; H. Iizuka; G. Pozzato; S. Mishiro (Archives of Virology, 1996)

Mapping of transcriptional regulatory domains of pseudorabies virus immediate-early protein - S. Taharaguchi; H. Inoue; E. Ono; H. Kida; S. Yamada; Y. Shimizu (Archives of Virology, 1994)

Identification of epitopes associated with different biological activities on the glycoprotein of vesicular stomatitis virus by use of monoclonal antibodies - S. Nagata; Y. Okamoto; T. Inoue; Y. Ueno; T. Kurata; J. Chiba (Archives of Virology, 1992)

Characterization of the beta-lactamase from Klebsiella pneumoniae - E. E. Stobberingh; R. Okamoto; M. Inoue; S. Mitsuhashi (Antonie van Leeuwenhoek, 1985)